Whose 'fault' is it? Becoming homeless in Singapore. (December 2018) - Tan, Harry; Forbes-Mewett, Helen
Singapore is a country that prides itself on providing cheap affordable public housing for its citizens. Nonetheless, the increased visibility of older people sleeping rough in public spaces has led to a contentious debate in recent years about why they are becoming homeless. The article first examines this debate from the different interpretations offered by the government, the national print media and local internet blogs and forums. Homelessness tends to be invariably attributed to personal problems for which the government is not held responsible or to broader structural problems resulting from government policies and bureaucracy. Our findings, from a two-year ethnographic study of older homeless people in Singapore, show that such one-sided causal explanations of homelessness are fundamentally flawed and provide inadequate explanations of why older people become homeless. Rather than asking whose fault is it, we adopt the pathways approach to highlight homelessness as a process involving personal decisions as well as structural factors. The article thus presents two key findings of our research. First, older people in our study did not become homeless from a specific pathway but encountered multiple pathways during their lives. Second, these older people began to sleep rough when the multiple pathways led to the weakening and subsequent loss of structural resources from work, family and friends and government assistance in Singapore.